Evaluation of Mast Cell Density in Mucoepidermoid Carcinoma and Pleomorphic Adenoma - Azadeh Jalili; Najmeh Jafari; Seyed Hosein Tabatabaei (Shiraz University of Medical Sciences, 2023)
Statement of the Problem: Mast cells are round to elliptical cells that originate from bone marrow stem cells and enter the peripheral blood. By releasing inflammatory mediators, these cells are involved in type I hypersensitivity, wound healing, defense against pathogens, increased blood vessel formation, and destruction of the extracellular matrix. There are contradictory results regarding the role of mast cells in tumor lesions.Purpose: Considering the contradictory results and few studies on the density of mast cells in salivary tumors, the present study investigated and compared the density of mast cells in two common salivary gland tumors.Materials and Method: In the cross-sectional study after reviewing the records of patients referred to the Pathology Department of the School of Dentistry and Shahid Sadoughi Hospital in Yazd, 15 blocks of each of the mucoepidermoid carcinoma and pleomorphic adenoma tumors were taken. After Giemsa staining of the samples, the average of stained cells in 10 random fields under 400× magnification was counted. The results were analyzed using statistical tests of t-test, ANOVA, Chi-square, and Mann-Whitney in SPSS ver. 22.Results: The average mast cell counts in pleomorphic adenoma (4.2) was higher than muco-epidermoid carcinoma (1.7) but there was no significant relationship (p= 0.305). In mucoepidermoid carcinoma, the numbers of mast cells increased with increasing tumor grade (low: 0/467 moderate: 1/567 high: 2/983) and there was a significant relationship (p= 0.009).Conclusion: According to the results of the present study, it seems that the mast cells accumulation may be secondarily associated with inflammatory responses due to cell accumulation and tissue destruction by tumor cells.